2010
DOI: 10.1109/lpt.2010.2048895
|View full text |Cite
|
Sign up to set email alerts
|

10-GHz All-Optical Gate Based on a III–V/SOI Microdisk

Abstract: Abstract-We demonstrate an ultra-fast and low power all-optical gate in pump-probe configuration based on free carrier induced refractive index modulation in a 5µm radius InP/InGaAsP microdisk heterogeneously integrated onto an SOI waveguide circuit. High speed gating is obtained by extracting the carriers from the microdisk active layer by applying a reverse bias. Measured transient responses show that this gate is capable of working up to 20GHz.Index Terms-Microdisk, Optical gate, SOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The fast switch-off time is due to fast recombination of free carriers owing to the high surface to volume ratio and rough side walls of the microdisk. Use of smaller diameter (7.5µm) of the microdisk here as compared to that in our previous work (10µm) [6] has contribution in faster switch-off time but at the same time we believe that the probe beam also acts as a seeding beam and contributes for faster response. It is observed that the extinction ratio increases with increasing pump power but the switch-off time also becomes larger.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…The fast switch-off time is due to fast recombination of free carriers owing to the high surface to volume ratio and rough side walls of the microdisk. Use of smaller diameter (7.5µm) of the microdisk here as compared to that in our previous work (10µm) [6] has contribution in faster switch-off time but at the same time we believe that the probe beam also acts as a seeding beam and contributes for faster response. It is observed that the extinction ratio increases with increasing pump power but the switch-off time also becomes larger.…”
mentioning
confidence: 75%
“…So far ultra-fast (of the order of 10 Gbps) alloptical switching, modulation and wavelength conversion in microrings/disks on the SOI platform has been demonstrated using reverse bias [2], ion implantation [4] and forward bias [5]. Realization of bias-free on-chip alloptical functions results in easy packaging of the chips due to the reduced number of pins required.In our previous work [6] we demonstrated 10GHz alloptical gating in a 10 µm diameter III-V/SOI disk but the use of reverse bias was necessary to achieve this speed and the extinction ratio was only 4.5dB. Using the same concept as in ref.…”
mentioning
confidence: 99%
See 3 more Smart Citations